Hubungan Antara Motivasi dengan Kemampuan Menghafal Al-Qur’an di SMK Negeri 1 Kebumen - Kurnianti, Fitria; Subarkah, Imam (Tarbi: Jurnal Ilmiah Mahasiswa, 2024)
This study aims to determine the relationship between motivation and the ability to memorize the Qur'an at State Vocational High School 1 Kebumen. The study was conducted by analyzing the relationship between motivation and the ability of students to memorize the Qur'an in the Tahfidz Program at State Vocational High School 1 Kebumen. The method used is qualitative research through questionnaires and documentation. The data analysis technique in this study used Pearson Product Moment Correlation. The results of the study indicate that: (1) Based on the results of the product moment correlation test between intrinsic motivation (X1) and memorization ability (Y), it can be seen that there is a positive relationship between variable X1 and variable Y. This is indicated by looking at rcount = 0.993 which is categorized as very strong or high. So Ha is accepted, namely there is a relationship between intrinsic motivation and the ability to memorize the Qur'an. (2) Based on the results of the product moment correlation test between extrinsic motivation (X2) and memorization ability (Y), it can be seen that there is a positive relationship between variable X2 and variable Y. This is indicated by looking at rcount = 0.986 which is categorized as very strong or high. So Ha is accepted, that is, there is a relationship between extrinsic motivation and the ability to memorize the Qur'an. The conclusion is that intrinsic motivation and extrinsic motivation have a very strong relationship with the ability to memorize the Qur'an. Therefore, intrinsic motivation and extrinsic motivation have a very strong influence on the success of memorizing the Qur'an.